The Influence Of Brand Image, Product Quality Perception And Price Perception On Purchase Intention In Somethinc Consumers In Malang - Ananda, Nadia Putri; Handayanto, Eko; Hilmi, Luqman Dzul (Jurnal Manajemen Bisnis dan Kewirausahaan, 2024)
This research is motivated by the existence of Somethinc products which are relatively new, but these products are able to compete with products that have long been in the market share. These good sales indicate a high purchase intention from consumers in Somethinc products so it can be formulated in this study that how consumers have purchase intention in Somethinc products amid the phenomenon of intense competition based on brand image, perceived product quality, and perceived price. This study aims to determine the effect of brand image, perceived product quality, and perceived price on purchase intention in Somethinc consumers in Malang City. This research uses quantitative methods. The sampling technique used was purposive sampling with a total sample of 152 Somethinc consumers in Malang City, especially in Lowokwaru District by distributing questionnaires. The analytical tool used in this research is multiple regression analysis. The results of this study concluded that Brand Image, Product Quality and have a positive and significant effect on Purchase Intention.